La dinamización de los procesos societarios para la reactivación económica - Younes Solórzano, Amira Salma (2022)
The COVID 19 pandemic significantly affects the economy of Ecuador, creating a chain effect in several sectors, which led to an increase in the unemployment rate and a considerable drop in income. This gave way to a considered number of actions that help the economic reactivation of the country. One of the sectors affected was the corporate sector, which through this article using an interdisciplinary methodology of a qualitative nature, with the support of quantitative indicators, analyzes the problem caused by the pandemic in this sector, in addition to determining the regulatory measures brought in Ecuador. in order to facilitate the corporate process, with the purpose of facilitating an economic reactivation in the country's corporate sector. Where simplified joint-stock companies also stand out above any of the different types of companies existing in Ecuadorian regulations, since for the reasons of the global COVID 19 pandemic they were part of the solution for the reactivation of the corporate sector in the country, since they offer as facilities the reduction of entry barriers for its constitution and exit for its registration cancellation, as well as for the eradication of the normative anachronistic imperativism in its operation…..